COMPOST PRODUCTION POTENTIAL FROM WASTE IN TANA TIDUNG REGENCY FINAL PROCESSING SITE (TPA) - Tini Parmawati; Endang Hernawan; Sri Listyarini (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
Tana Tidung Regency is predominantly an agricultural area, with around 61.51 percent of the total land area of the district dedicated to agricultural purposes, which amounts to 297,028.7 hectares. Despite having an FDS(Final Disposal Site) that spans roughly four hectares and is managed through a sanitary landfill system, the region still uses an open dumping system. The organic waste found in the FDS can be converted into compost, which can be utilized to fulfill the fertilizer needs of farmers in the Tana Tidung Regency. The primary aim of this study is to determine the compost production potential in Tana Tidung Regency. The research was conducted from May 2022 to January 2023, relying solely on secondary data. The secondary data utilized was waste pile data from the last five years, obtained from the Waste Sector of the Tana Tidung Regency Environmental Department. The data on waste is presented in graphical form, while the compost data projection analysis employs the provisions of Zulfinar and Sembiring (2015) in three scenarios: pessimistic, moderate, and optimistic. Based on the study's findings, the volume of waste generated in Tana Tidung Regency in 2022 will amount to 24,675,825 liters, with a total landfill of 24,676 tons. In the pessimistic scenario, no waste processing into compost will occur in 2022, while the moderate scenario estimates 17,273 tons, and the optimistic scenario estimates 19,741 tons.Key words: Compost, Moderate, Optimistic, Organic, and Pessimistic